Mental Health Literacy and Ontario Young People: Major Depressive Disorder, Bipolar Disorder, and Generalized Anxiety Disorder - Manser, Christine Jayme (My University, 2016)
This study examined the mental health literacy of a group of young people, with particular interest to their ability to correctly label, identify symptoms, and recommend appropriate help sources for Major Depressive Disorder, Generalized Anxiety Disorder, and Bipolar Disorder. Respondents were 88 Ontario, Canada residents (26 males, 62 females) aged 18-24. Respondents provided mixed knowledge in ability to determine whether an individual was dealing with mental illness as well as mixed knowledge in labeling the mental disorders examined and identifying the symptoms of each disorder. Respondents were significantly more likely to correctly label Major Depressive Disorder opposed to Generalized Anxiety Disorder and Bipolar Disorder. As well, respondents were significantly more likely to label appropriate symptoms for Major Depressive Disorder opposed to Generalized Anxiety Disorder and Bipolar Disorder. Our findings suggest that young people have a greater mental health literacy for Major Depressive Disorder opposed to Generalized Anxiety Disorder and Bipolar Disorder. Results are discussed in light of prior adolescent and young adult mental health literacy and clinical implications.
Keywords: Mental health; Mental health literacy; Major depressive disorder; Bipolar disorder; Generalized anxiety disorder; Mental illness in young people